Serum amyloid A3 exacerbates cancer by enhancing the suppressive capacity of myeloid‐derived suppressor cells via TLR2‐dependent STAT3 activation. Issue 6 (17th April 2014) - Lee, Jung‐Mi; Kim, Eun‐Kyung; Seo, Hyungseok; Jeon, Insu; Chae, Min‐Ji; Park, Young‐Jun; Song, Boyeong; Kim, Yun‐Sun; Kim, Yeon‐Jeong; Ko, Hyun‐Jeong; Kang, Chang‐Yuil
<x xml:space="preserve">Abstract</x> Myeloid‐derived suppressor cells (MDSCs), which suppress diverse innate and adaptive immune responses and thereby provide an evasion mechanism for tumors, are emerging as a key population linking inflammation to cancer. Although many inflammatory factors that induce MDSCs in the tumor microenvironment are known, the crucial components and the underlying mechanisms remain elusive. In this study, we proposed a novel mechanism by which serum amyloid A3 (SAA3), a well‐known inflammatory factor, connects MDSCs with cancer progression. We found that SAA3 expression in BALB/c mice increased in monocytic MDSCs (Mo MDSCs) with tumor growth. The induction of SAA3 by apo‐SAA treatment in Mo MDSCs enhanced their survival and suppressive activity, while it inhibited GM‐CSF‐induced differentiation. Endogenous SAA3 itself contributed to the increase in the survival and suppressive activity of Mo MDSCs. We demonstrated that SAA3 induced TLR2 signaling, in turn increasing the autocrine secretion of TNF‐α, that led to STAT3 activation. In addition, activated STAT3 enhanced the suppressive activity of Mo MDSCs. Furthermore, SAA3 induction in Mo MDSCs contributed to accelerating tumor progression in vivo. Collectively, these data suggest a novel mechanism by which Mo MDSCs mediate inflammation through SAA3‐TLR2 signaling and thus exacerbate cancer progression by a STAT3‐dependent mechanism.